A case of fatal acute fatty liver of pregnancy and literature review - Perera, Irushna Antonette; Pradeepan, Jebananthy Anandaselvam; Mayorathan, Uruthirapasupathy; Kumanan, Thirunavukarasu; Muhunthan, Kopalasuntharam; Selvaratnam, Gowry (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
AFLP, though rare, is an obstetric emergency which carries a high incidence of maternal and perinatal mortality, despite optimal care. We report a case of a 23-year-old primi mother, who presented to us with vague symptoms of feeling unwell and abdominal pain, was diagnosed with AFLP, and was managed accordingly with the highest level of care available but succumbed a few days into her illness though timely delivery was able to save the baby. By this case report we once again wish to emphasize the value of a timely diagnosis with a high level of clinical suspicion and supportive laboratory investigations including imaging; the need for early termination of pregnancy; and adequate supportive care as the key management options for AFLP. Further, we wish to explore the current treatment options available for AFLP and discuss a few novel therapeutic strategies such as plasma exchange in treating such cases and the pros and cons associated with these treatment modalities.